1983
DOI: 10.1037/0022-006x.51.5.718
|View full text |Cite
|
Sign up to set email alerts
|

Influence of psychotherapy research on clinical practice: An experimental survey.

Abstract: Psychologists evaluated a study that demonstrated the effectiveness of a child clinical treatment. The psychotherapy study varied on the described methodology, the childhood disorder treated, and the presence of information regarding the clinical significance of the findings. The true experimental version received higher methodology ratings than did the quasiexperimental and nonexperimental versions, and the version that reported the findings' clinical significance received higher methodology ratings than did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…What media of dissemination will guide practitioners' transitions to empirically based practice? Numerous studies have demonstrated that practicing clinicians are largely influenced by books on psychotherapy, discussions with colleagues, and clinical workshops (Barlow, Hayes, & Nelson, 1984; Cohen, 1979; Sargent & Cohen, 1983). Treatment manuals are thus well situated to provide both clinically relevant material for practicing clinicians, and dissemination of an empirically supported base of effective interventions.…”
Section: The Evolution Of Treatment Manualsmentioning
confidence: 99%
“…What media of dissemination will guide practitioners' transitions to empirically based practice? Numerous studies have demonstrated that practicing clinicians are largely influenced by books on psychotherapy, discussions with colleagues, and clinical workshops (Barlow, Hayes, & Nelson, 1984; Cohen, 1979; Sargent & Cohen, 1983). Treatment manuals are thus well situated to provide both clinically relevant material for practicing clinicians, and dissemination of an empirically supported base of effective interventions.…”
Section: The Evolution Of Treatment Manualsmentioning
confidence: 99%